SOLVING MATHEMATICAL PROBLEMS BY HIGH SCHOOL STUDENTS AS AN EFFECTIVE TOOL FOR DEVELOPING THE COMPETENCE OF «ENTREPRENEURSHIP AND FINANCIAL LITERACY» - Tkach, Olena (Physical and Mathematical Education, 2025)
The article highlights the methodological aspects of solving applied problems in mathematics lessons to form the competence «entrepreneurship and financial literacy»; the stages of solving such problems are given. Formulation of the problem. Considering the current trends in technology development, the digitalization of Ukraine’s population, and the desire to enhance financial literacy, changes are occurring in educational trends. Today, the State Standard of Basic Secondary Education and the State Standard of Specialized Secondary Education are built on a competency-based approach. One of the key competencies is «entrepreneurship and financial literacy», which implies a person’s ability to initiate, plan, and implement ideas, take responsibility, find opportunities and resources to achieve their goals, be able to effectively manage their own finances, use banking products, and make financial decisions. Considering regulatory documents, a modern teacher must find effective means and methods to implement the assigned tasks. Materials and methods. A combination of methods was employed in this study: theoretical, for analyzing regulatory documents, and empirical, involving pedagogical observation of the educational activities of 10th–11th grade students while they solved problems. Results. The study presents an example of a competency-based problem scenario tailored to the age-specific characteristics of high school students and designed to motivate them to solve the problem and independently seek information. The stages of solving applied problems are identified to effectively develop the competence of «entrepreneurship and financial literacy». Conclusions. Solving applied problems with financial content has proven effective in developing the competence of «entrepreneurship and financial literacy» among high school students. The use of relevant data, QR codes, and educational discussions enhances student motivation, fosters critical thinking, and transforms mathematics into a valuable tool for making informed financial and entrepreneurial decisions in real life.